Analysis of peripheral blood T-cell subsets and regulatory T-cells in multiple myeloma patients - Huang, Lai-quan; Wang, Jian-xin; He, Kun; Jiang, Yi-zhi; Wei, Zhong-ling; Huang, Dong-ping; Chu, Li-li (Cellular and Molecular Biology, 2018)
To study the peripheral blood T-cell subsets and regulatory T-cells of multiple myeloma (MM) patients. 48 MM patients and 24 healthy controls were enrolled. Changes in peripheral blood T-cell subsets in the MM patients i.e. CD4+CD25+T cells and CD4+CD25+CD127lowT regulatory cells (CD4+CD25+CD127lowTregs) and in healthy controls were measured using flow cytometry and immunohischemistry. The total T-cells (CD3+) in peripheral blood lymphocyte and auxiliary/induced T-cells (CD3+CD4+ T cell) of the 48 MM patients showed no statistical significance when compared with those of the control group. Suppressor/cytotoxicity T-cells (CD3+CD8+ T cell) increased (p < 0.05). CD4+CD25+T cells and CD4+CD25+CD127low Tregs were significantly higher than corresponding values in the healthy group (p < 0.05). The CD4+/CD8+ T cell ratio of Stage III MM patients was significantly lower than that of the control group (p < 0.05). The CD4+CD25+T cells and CD4+CD25+CD127low Tregs of MM patients in the stable and the progressive stages were significantly higher than those of MM patients in the control group (p < 0.05). The abnormality of the peripheral blood T-cell subset, increased expression of CD4+CD25+CD127low Tregs, and low cellular immunity of MM patients are related to clinical staging and progression of the disease. The quantity of CD4+CD25+CD127lowTregs of peripheral blood cells of MM patients could be significantly increased through the inhibition of CD4+ and CD8+T cell activities. CD4+CD25+CD127low Tregs promotes tumor growth through the inhibition of immunologic cell proliferation. Immunological dysfunction based on Tregs cells plays an important role in the pathogenic course.